2014
DOI: 10.1016/j.neuroimage.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Detecting resting-state brain activity by spontaneous cerebral blood volume fluctuations using whole brain vascular space occupancy imaging

Abstract: Resting-state brain activity has been investigated extensively using BOLD contrast. However, BOLD signal represents the combined effects of multiple physiological processes and its spatial localization is less accurate than that of cerebral blood flow and volume (CBF and CBF, respectively). In this study, we demonstrate that resting-state brain activity can be reliably detected by spontaneous fluctuations of CBV-weighted signal using whole-brain gradient and spin echo (GRASE) based vascular space occupancy (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…Activity of the thalamic clusters from the K = 7 parcellation showed responses in certain clusters to visuomotor stimulation that are consistent with previous reports of visuomotor task activation (Calhoun et al, 2001;Miao et al, 2014;Witt et al, 2008), providing validity of our thalamic parcellation results. Specifically, Clusters 2, Cluster 3 and Cluster 5 were activated during the visuomotor task.…”
Section: Visuomotor Task Activationsupporting
confidence: 92%
“…Activity of the thalamic clusters from the K = 7 parcellation showed responses in certain clusters to visuomotor stimulation that are consistent with previous reports of visuomotor task activation (Calhoun et al, 2001;Miao et al, 2014;Witt et al, 2008), providing validity of our thalamic parcellation results. Specifically, Clusters 2, Cluster 3 and Cluster 5 were activated during the visuomotor task.…”
Section: Visuomotor Task Activationsupporting
confidence: 92%
“…These findings are in line with resting-state MRI measurements of blood flow and blood volume (Miao et al, 2014;Zhu et al, 2013;Zou et al, 2009), whereby typical low-frequency and connectivity patterns were observed. The findings obtained in this work indicate greater value in blood-oxygenation-based fcMRI compared with CBF-or CBV-sensitive fcMRI for reporting neuronal connectivity.…”
Section: Fig 5 (A)supporting
confidence: 88%
“…Changes in vascular function or oxidative metabolism may occur with or without changes in neural activity. Although some studies have explored physiological correlates of low-frequency fluctuations (De Luca et al, 2006;Miao et al, 2014;Wu et al, 2009;Zou et al, 2009), fundamental gaps remain regarding the relationship between these fluctuations and brain function, including the relative contributions of neuronal and vascular factors to the measured fcMRI time series. A complicating factor is that vascular smooth muscle is known to have slow contractile rhythms, termed vasomotion, around this frequency range (Mayhew et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the technique has been used successfully at UHF (38) for laminar specific applications (9, 10). 3D GRASE can also be used as readout sequence in CBV imaging, as used at low resolutions for fMRI at 3T (39–41) and in resting state experiments (42, 43). However, VASO 3D GRASE has not been developed or evaluated for mesoscale high resolution CBV-fMRI.…”
Section: Introductionmentioning
confidence: 99%